A Search for Evidence of a Direct Relationship between Tinnitus and Suicide - Jacobson, Gary P.; McCaslin, Devin L. (Journal of the American Academy of Audiology, 2001)
The purpose of this investigation was to determine whether there exists in the scientific literature support for a cause and effect relationship between tinnitus and suicide. MEDLINE and HealthStar databases were queried using the combined search terms “tinnitus” and “suicide” over the time period from 1966 to 2001 for MEDLINE and from 1975 to 2001 for HealthStar. Foreign-language reports were included if they had been translated into English or, at least, if they contained an English-language translation of the abstract. A total of three published reports pertinent to this topic were recovered. None of these reports showed a causal relationship between tinnitus and suicide. More often, patients who had attempted or committed suicide had significant preexisting psychiatric conditions, the most common being depression. Accordingly, it is our conclusion that nowhere in the existing literature is there any evidence supporting a cause and effect relationship between tinnitus and suicide.
Keywords: Depression; suicide; tinnitus